2018
DOI: 10.1111/jcmm.13669
|View full text |Cite
|
Sign up to set email alerts
|

The role of K63‐linked polyubiquitination in cardiac hypertrophy

Abstract: Ubiquitination, also known as ubiquitylation, is a vital post‐translational modification of proteins that play a crucial role in the multiple biological processes including cell growth, proliferation and apoptosis. K63‐linked ubiquitination is one of the vital post‐translational modifications of proteins that are involved in the activation of protein kinases and protein trafficking during cell survival and proliferation. It also contributes to the development of various disorders including cancer, neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 104 publications
(210 reference statements)
0
7
0
Order By: Relevance
“…9 The K63-linked ubiquitination is crucial in the regulation of pathways such as NF-κB (nuclear factor–κB), which is implicated in the development and progression of cardiac hypertrophy. 30 Researchers have begun to characterize the remaining, “atypical” Ub sites (linked through M1, K6, K11, K27, K29, or K33) by specific E3 Ub ligases. 31,32 For example, K27- and K29-linked ubiquitylation has been associated with lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…9 The K63-linked ubiquitination is crucial in the regulation of pathways such as NF-κB (nuclear factor–κB), which is implicated in the development and progression of cardiac hypertrophy. 30 Researchers have begun to characterize the remaining, “atypical” Ub sites (linked through M1, K6, K11, K27, K29, or K33) by specific E3 Ub ligases. 31,32 For example, K27- and K29-linked ubiquitylation has been associated with lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of autophagic mechanisms by K63-linked polyubiquitination has been linked to many pathological processes such as neurodegenerative and cardiovascular diseases, cancer progression, accelerated aging mechanisms and different kinds of infections (Gao et al 2021;Lim and Lim 2011;Liu et al 2018;Yan et al 2018).…”
Section: Medical Outlookmentioning
confidence: 99%
“…It has been reported that Lys63‐linked Ub chains regulate various cellular events, including DNA damage repair (DDR), signal transduction, protein trafficking, and immune response. Misregulation of these pathways leads to stress, accumulation of mutations, cell cycle arrest, and apoptosis that can result in various pathological conditions 33 .…”
Section: Resultsmentioning
confidence: 99%